IT Professional Work Style Risk Factors for Work-Related Musculoskeletal Disorders - Rahma, Ratih Andhika Akbar; Rahmania, Aisy; Arifah, Dian Afif; Prasetya, Tofan Agung Eka; Samad, Nurul Izzah Abdul; Al Mamun, Abdullah (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2024)
Information Technology (IT) professionals suffer musculoskeletal problems and injuries more frequently due to their type of work which makes them rely on using computers for a prolonged time. The goal of this study is to analyze the risk factors for work-related musculoskeletal disorders in IT professionals. Amount of 150 IT professionals participated in this study as respondents. The Cornell Musculoskeletal Disorders Questionnaire (CMDQ) was used as a measurement tool in determining musculoskeletal complaints among IT professionals. The independent variables (age, gender, working experience, educational level, number of hours spent at work in front of a computer per day, working hours, and exercise habits) that significantly affected the variance in the dependent variable (musculoskeletal disorders) were evaluated using multiple linear regression analysis (p-value < 0.05). IT professionals reported experiencing symptoms most frequently 3–4 times per week in the upper back (45.3%) and back (31.3%), and once or twice per week in the upper back (33.3%) and back (31.3%). Then on the discomfort level, IT professionals feel very uncomfortable in the back (71.3%), upper back (68.7%), and neck (64%). The number of hours spent at work in front of a computer per day (p-values of 0.040) and working hours (p-value of 0,032) are significant predictors of IT professional musculoskeletal disorders. IT professionals reported experiencing the greatest musculoskeletal issues in the right upper extremity, which comprises the right wrist, right forearm, right shoulder, and right upper arm (88%). Back (84%) and left lower extremities (82.7%), which include the left thigh, left knee, and left lower legs, are two other issues that most IT professionals have.